2007
DOI: 10.1245/s10434-007-9356-1
|View full text |Cite
|
Sign up to set email alerts
|

Detecting Occult Malignancy in Prophylactic Mastectomy: Preoperative MRI Versus Sentinel Lymph Node Biopsy

Abstract: MRI adds great cost and misses most occult cancers in PMs. SLNB allows the rare patient with occult IDC to avoid axillary dissection but adds cost. Given the low rate of unsuspected invasive cancers and the costs of MRI and SLNB, neither is recommended as standard practice for PM patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
44
1
2

Year Published

2007
2007
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(48 citation statements)
references
References 17 publications
1
44
1
2
Order By: Relevance
“…Of these studies, the data of 1 study 16 were updated by McLaughlin and colleagues 17 in 2008, and 1 study 18 was prospective, leaving 6 studies for inclusion in our analysis. The data were extracted from these 6 studies 17,[19][20][21][22][23] (Fig. 1).…”
Section: Resultsmentioning
confidence: 99%
“…Of these studies, the data of 1 study 16 were updated by McLaughlin and colleagues 17 in 2008, and 1 study 18 was prospective, leaving 6 studies for inclusion in our analysis. The data were extracted from these 6 studies 17,[19][20][21][22][23] (Fig. 1).…”
Section: Resultsmentioning
confidence: 99%
“…Sentinel lymph nodes are likely involved in the spread of tumor cells and therefore the status of these nodes are seen as an independent additional factor in the prognosis in disease (1). Diagnostic techniques such as ultrasound, magnetic resonance imaging and histological confirmation (biopsy) are used to investigate a possible metastasis to the sentinel lymph nodes (2)(3)(4). In the case of head and neck cancer, where a metastasis is confirmed, the removal of the sentinel lymph node is the primary option to increase the survival rate of the patient (5).…”
Section: Publications Digest Ultrasound and Nano/microbubbles For Molmentioning
confidence: 99%
“…As an example, the work of Karakatas et al (20) was used, who showed in their publication a mitochondrion covered with 565 gold nanoparticles (13 nm diameter). From the calculations it was concluded that the dose enhancement ratios [1] were the highest in the kilovolt range, [2] depend on the dimensions of the mitochondrion, [3] the number of gold nanoparticles, and [4] the thickness of the gold nanoparticle coating. The presented work suggests further investigation of the role of the mitochondrium in cellular response to radiation and a novel possibility for radiation therapy where the mitochondria are the target.…”
Section: Targeting Mitochondria In Cancer Cellsmentioning
confidence: 99%
“…La mé ta-analyse de 2007 montre que l'association d'A-LHRH à la chimiothé rapie avec ou sans adjonction de tamoxifè ne ré duit le risque de ré cidive de 12,2 % (IC 95 % : [0, [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22]6] ; p = 0,04).…”
Section: Recommandations De Prescriptionsunclassified
“…Le bon pronostic et la rareté des lé sions dé couvertes sur les piè ces de mastectomie prophylactique semblent ne pas justifier la ré alisation systé matique d'une procé dure de ganglion sentinelle sur le sein indemne [22,26] (niveau de preuve 4).…”
Section: Annexectomie Bilaté Rale (Accord D'experts)unclassified